Delayed Presentation of Submucosal Retained Toothbrush from Self-Inflicted Injury in Patient with Schizophrenia. (31st December 2017) - Creswell, Caleb H.; Kille, Tony L.; Hoffman, Matthew R.; Kennedy, Tabassum; Dailey, Seth H.
Abstract : Foreign body ingestion occurs in not only children but also adults, particularly those with history of neurologic disease, alcohol use, or psychiatric disease. We present the case of a 40-year-old male with schizophrenia who presented to the emergency room with a long history of pharyngeal foreign body sensation which had recently progressed to include trismus, odynophagia, and dyspnea. Flexible laryngoscopy demonstrated fullness of the right posterior pharyngeal wall and computed tomography (CT) showed a linear opaque foreign body extending from the level of the oropharynx to the thyroid ala. Further history elicited that he stabbed himself in the pharynx two years prior with a toothbrush following a command hallucination. The toothbrush was removed uneventfully via an external approach. The patient was discharged with psychiatry follow-up. This case is unusual due to the submucosal location of the foreign body and the length of retention. It demonstrates the atypical nature which patients with comorbid psychiatric illness may present following foreign body injury and the use of an external surgical approach for the removal of a retained foreign body based on CT reconstruction.